Detecting neuroinflammation in the brain following chronic alcohol exposure in rats: A comparison between in vivo and in vitro TSPO radioligand binding. (25th March 2019) - Tyler, Ryan E.; Kim, Sung Won; Guo, Min; Jang, Yeon Joo; Damadzic, Ruslan; Stodden, Tyler; Vendruscolo, Leandro F.; Koob, George F.; Wang, Gene‐Jack; Wiers, Corinde E.; Volkow, Nora D.
Abstract: Excessive alcohol consumption is associated with neuroinflammation, which likely contributes to alcohol‐related pathology. However, positron emission tomography (PET) studies using radioligands for the 18‐kDa translocator protein (TSPO), which is considered a biomarker of neuroinflammation, reported decreased binding in alcohol use disorder (AUD) participants compared to controls. In contrast, autoradiographic findings in alcohol exposed rats reported increases in TSPO radioligand binding. To assess if these discrepancies reflected differences between in vitro and in vivo methodologies, we compared in vitro autoradiography (using [ 3 H]PBR28 and [ 3 H]PK11195) with in vivo PET (using [ 11 C]PBR28) in male, Wistar rats exposed to chronic alcohol‐vapor (dependent n = 10) and in rats exposed to air‐vapor (nondependent n = 10). PET scans were obtained with [ 11 C]PBR28, after which rats were euthanized and the brains were harvested for autoradiography with [ 3 H]PBR28 and [ 3 H]PK11195 ( n = 7 dependent and n = 7 nondependent), and binding quantified in hippocampus, thalamus, and parietal cortex. Autoradiography revealed significantly higher binding in alcohol‐dependent rats for both radioligands in thalamus and hippocampus (trend level for [ 3 H]PBR28) compared to nondependent rats, and these group differences were stronger for [ 3 H]PK11195 than [ 3 H]PBR28. In contrast, PET measures obtained in the same rats showed no group difference in [ 11 C]PBR28 binding. Our in vitro data are consistent with neuroinflammation associated with chronic alcohol exposure. Failure to observe similar increases in [ 11 C]PBR28 binding in vivo suggests the possibility that a mechanism mediated by chronic alcohol exposure interferes with [ 11 C]PBR28 binding to TSPO in vivo. These data question the sensitivity of PBR28 PET as a methodology to assess neuroinflammation in AUD. Abstract : Rats made alcohol dependent following 6–10 weeks of intermittent alcohol‐vapor exposure were assessed for neuroinflammation in the brain using PET and autoradiography with TSPO‐selective radioligands, a biomarker of glial activation in the brain. Autoradiography results using [3H]PBR28 and [3H]PK11195 show elevated binding in alcohol‐dependent compared to non‐dependent rats, but PET data using [11C]PBR28 show no differences in binding between alcohol‐dependent and non‐dependent rats from the same animals. This discrepancy questions the sensitivity of [11C]PBR28 PET to assess neuroinflammation in alcohol exposure.